2005
DOI: 10.1139/x05-022
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and population characteristics of dwarf mistletoe infected trees in an old-growth Douglas-fir – western hemlock forest

Abstract: We investigated the distribution and severity of trees infected with western hemlock dwarf mistletoe (Arceuthobium tsugense (Rosendahl) G.N. Jones subsp. tsugense) in an old-growth Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) -western hemlock (Tsuga heterophylla (Raf.) Sarg.) forest. With the use of Hawksworth six-class dwarf mistletoe rating system, infection status was assessed for 3516 hemlock and true firs ≥5 cm diameter on a 12-ha stem-mapped plot located in the Cascade Mountains of southwest Washin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…With respect to crown spread size susceptibility, some patterns agree with what was expected: most of the uninfected trees were the smallest ones and MDMR increased with tree size (Shaw et al, 2005). Young trees are rarely parasitized because they cannot provide enough resources to the parasite and the consequences for them are mostly lethal (Press, 1995); however, a larger tree represents a better resource because it has a larger surface for seed reception (Arriaga et al, 1988;Hernández-Benítez et al, 2005) and can bear a larger load of parasites declining in health but not in mortality (Musselman and Press, 1995;Hawksworth and Wiens, 1996).…”
Section: Pinus Hartwegii Growth Parasitized By Dwarf Mistletoesupporting
confidence: 82%
See 1 more Smart Citation
“…With respect to crown spread size susceptibility, some patterns agree with what was expected: most of the uninfected trees were the smallest ones and MDMR increased with tree size (Shaw et al, 2005). Young trees are rarely parasitized because they cannot provide enough resources to the parasite and the consequences for them are mostly lethal (Press, 1995); however, a larger tree represents a better resource because it has a larger surface for seed reception (Arriaga et al, 1988;Hernández-Benítez et al, 2005) and can bear a larger load of parasites declining in health but not in mortality (Musselman and Press, 1995;Hawksworth and Wiens, 1996).…”
Section: Pinus Hartwegii Growth Parasitized By Dwarf Mistletoesupporting
confidence: 82%
“…The stand structure is strongly associated with dwarf mistletoe dynamics, where it has been shown that the crown volume and size of the dominant cohort decreases with infection intensity (Shaw et al, 2005;Agne et al, 2014). These hemiparasitic plants form a complex rootlike structure, called haustorium, which is the organ of contact with the hosts' xylem and phloem .…”
mentioning
confidence: 99%
“…Most notable, and well studied, in this regard are the dwarf mistletoes in conifers of western North America (198). Severe dwarf mistletoe infestations alter forest stand structure by creating gaps due to mistletoe-associated mortality and branch and tree-top dieback (92), creating patchiness in the stand due to the clumped nature of dwarf mistletoe infection centers (197), and reorganizing vertical canopy structure so that more foliage is concentrated in the lower canopy (76,77). Succession is influenced by mortality of host species and the interaction of dwarf mistletoes, fire, and fire suppression (92,197,203).…”
Section: Mistletoe-ecosystem Interactionsmentioning
confidence: 99%
“…46 Dwarf-mistletoes (genus Arceuthobium) that are considered to be dependent on host-derived organic carbon (based on gasometric measurements; 47,48 no detailed carbon budget studies are available) tend to perform better on vigorous host that are in a good physiological state. 48,49 Nonetheless, even these highly heterotrophic species were demonstrated to produce more aerial shoots under high irradiance which is however not likely to be underpinned by a causal dependence of parasite performance on the light level. It is more probable that the dwarf-mistletoe is indirectly positively affected by increased photosynthetic capacity of highly irradiated branch or by elevated temperature.…”
Section: Heterotrophic Carbon Gainmentioning
confidence: 99%